PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWAKELAS VA SD NEGERI 136 PEKANBARU - Dani Syahpitri Ginting Syahpitri Ginting; Hendri Marhadi Marhadi; Damanhuri Daud Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem on this research is that low students’ achievement on social science in fifth graderes at SD Negeri 136 Pekanbaru within average score 64,34 and clasical completenes 25% within minimal completenes criterion stated is 70. The purpose of this research is to improve students’ achievement on social science of the fifth graderes in SD Negeri 136 Pekanbaru with the application of cooperatif learning model type jigsaw. This research was classroom action research consisting 2 cycles within 4 procedures: planning, doing, observing, and reflecting, and each cycle consists of three meetings. Instrumen on this research are sylabus, lesson plan, and student work sheet. Instruments for collecting data are observation sheet and test. Data which was collected were learning out comes and teacher’s activities during the lessons. After imlpementation of cooperatif learning model type Jigsaw it was abtained students’ outcomes in UAS I within average 69,75 (improved from basic score 32,5%) with classicall completeness 57,5%. The average score form UAS II was 82,75 (improved 62,5%) with classicall completeness 87,5%. Teacher activities results in the cycle was 75% (good category). Meanwhile in the cycle II was 100% (very good category). Students activity in the cycle I was 81,6% (very good category), and then in the cycle II was 93,65% (very good category). Based on this result it can be concluded that the implementation of cooperatif learning model type Jigsaw can social science in fifth graderes at SD Negeri 136 Pekanbaru. Keywords: Cooperatif Jigsaw, Students Achievement the Result Of Social Students